2021
DOI: 10.1186/s12876-021-01865-8
|View full text |Cite
|
Sign up to set email alerts
|

Normal values for high-resolution anorectal manometry in healthy young adults: evidence from Vietnam

Abstract: Background High-resolution anorectal manometry (HRAM) has been developed to improve measurement of anorectal functions. This study aims to identify normal HRAM values in healthy young Vietnamese adults. Methods We conducted a cross-sectional study at the National Hospital of Traditional Medicine (Hanoi, Vietnam) from July through December 2014. Healthy young adults were invited to participate in the study. All anorectal measurement values were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Furthermore, our method provided acceptable defecation function. The measurements obtained by manometry, maximum resting pressure, maximum squeeze pressure, and the length of the high-pressure zone yielded similar results compared to reported normal values (9) at two years after surgery. Recovery of the length of the highpressure zone seems to be significantly involved in the noted Wexner score improvements.…”
Section: Discussionsupporting
confidence: 72%
“…Furthermore, our method provided acceptable defecation function. The measurements obtained by manometry, maximum resting pressure, maximum squeeze pressure, and the length of the high-pressure zone yielded similar results compared to reported normal values (9) at two years after surgery. Recovery of the length of the highpressure zone seems to be significantly involved in the noted Wexner score improvements.…”
Section: Discussionsupporting
confidence: 72%
“…However, defining "normal" resting and squeeze pressures for ARM values is quite difficult. There is obviously an overlap since several studies showed different values for normal and abnormal resting and squeeze pressures for ARM [14,[23][24][25][26][27][28]. To be accurate in comparing between groups, the pressures should be adjusted according to age, gender, and parous and nulliparous females.…”
Section: Discussionmentioning
confidence: 99%
“…Figures 1 and 2 show examples of the pressure profile during rest (MBP) and during squeeze (MSP) with ManoView. Normal values have been published by several authors and show a large range [14,[23][24][25][26][27][28]. Based on these studies, we considered an anal rest or squeeze pressure lower than 50 mmHg as "low."…”
Section: D High-resolution Anal Manometry (3d-hram)mentioning
confidence: 99%
“…After searching the PubMed database, we have been able to identify few studies which quantify HRAM parameters in the general population, notably the study by Carrington et al [2], Lee et al [3], Deshmukh et al [4] and Le Manh Cuong et al, [5]. All these studies have been conducted on healthy, asymptomatic adults.…”
Section: Introductionmentioning
confidence: 99%
“…All these studies have been conducted on healthy, asymptomatic adults. The number of patients included ranges from 30 [5], to 115 [2]. Because the type of catheter greatly influences the values recorded, a comparison of the normal values reported in these studies is not possible as different types of catheters were used (ISOLAB, Diversatek, Unisensor).…”
Section: Introductionmentioning
confidence: 99%